Prison Privatization: An Empirical Literature Review and Path Forward - Kim, Dae-Young (International criminal justice review, 2022)
A substantial body of literature has been devoted to examine the efficacy of prison privatization. Unfortunately, the empirical findings to date are equivocal regarding whether prison privatization fulfills its promises and our expectations of cost efficiency, prison quality, postrelease success, nonprofit prison privatization, system-wide improvement in corrections, local economic development, and determinants of privatizing prisons. Such inconclusive evidence may result from the shortcomings of past research, and thus there is a continuing need for more work using a wide range of data sources and research designs. This article conducts a review of empirical research, discusses conceptual and methodological problems in the literature, and offers guidance for future research. It may not only stimulate additional research but also inform public policy decision-making on prison privatization.